If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=p-2(6p+5)
We simplify the equation to the form, which is simple to understand
12=p-2(6p+5)
Reorder the terms in parentheses
12=p+(-12p-10)
Remove unnecessary parentheses
+12=+p-12p-10
We move all terms containing p to the left and all other terms to the right.
-1p+12p=-10-12
We simplify left and right side of the equation.
+11p=-22
We divide both sides of the equation by 11 to get p.
p=-2
| x^3-3x^2-6x=20 | | p^2-7p+6= | | -x^2-18=x^2+12x | | -(3+8x)=-51 | | 5x+40=9x-24 | | 4y=456-2x | | a-10=-3 | | 10x^2-4=6x^2+5 | | 3+4=14 | | 3(2n+8)=-18 | | x-4+8x=6x-16 | | y^2-4y+4= | | 2m^2=21m | | -5x^2+16x-3=0 | | 4x^3-27x^2-11x-1=0 | | 4x^2-49= | | -x^2-12x+5=0 | | y=1-x-x^2 | | 3x^2+3x+11=0 | | 35q=-5 | | 3x^2+12x+27=0 | | 65=-4-3(1+3r) | | w/4-4=3 | | 4x+2y=456 | | 4x+2x=456 | | -10x+6=3x+12 | | 4.9x^2-25x-70=0 | | 4(2+p)=32-3(p+1) | | 14=-7(1+3r) | | 14=-7(2+3r) | | 2x+5y+9z+3x+2y-6z-4x-7y+2z= | | -4x^2+11x-6=0 |